Behind the scenes : contemporary Bollywood directors and their cinema - Viswamohan, Aysha Iqbal; John, Vimal Mohan (New Delhi, India ; Thousand Oaks, California : SAGE Publications India Pvt Ltd, 2017)
For those who think, read, teach, and write about Bollywood, this book is the release of the year!
11 Globalization, Reflexivity and Genre in Zoya Akhtar's Films12 Urban Dreams; 13 Ashutosh Gowariker; 14 Madhur Bhandarkar and the New Bollywood Social; Part III Gendered Cinema; 15 Finding Femininity; 16 Gender Politics and Small-town India; 17 Women in the Dark World; 18 'There Is No Greater Joy than Telling a Story One Believes In'-Our Brother Onir; 19 Location and Agency in Crafting Habib Faisal's Authorship; Glossary; Filmography; Bibliography; About the Editors and Contributors; Index.
Contributed articles.
Includes bibliographical references, filmography and index.
Online resource; title from PDF title page (EBSCO, viewed January 18, 2017).
eBooks on EBSCOhost
Keywords: Motion pictures -- India -- History; Motion picture industry -- India -- Mumbai -- History; Motion picture producers and directors -- India; Cinéma -- Inde -- Histoire; Producteurs et réalisateurs de cinéma -- Inde; PERFORMING ARTS -- Reference; Motion picture industry; Motion picture producers and directors; Motion pictures; India; India -- Mumbai; History